O Corpo Ganha Lugar Na Educação Inclusiva: Um Olhar Para A Motricidade No Transtorno Do Espectro Do Autismo (TEA) (Global Journal of Human-Social Science, 2021)
This research concerns to Autism Spectrum Disorder (ASD) children and adolescents teachinglearning process Disorder (ASD) children and adolescents with emphasis on the student's potential and not what is lacking. The main aims of this study are for analyzing the importance of motor skills for the ASD learner to develop, as well as to discuss the inclusive perspective and to reflect on the traditional teaching method and on a teaching that treats the body in a perspective seen in a broader and less stereotyped language, referring to Henri Wallon readings who guides the work with the human being in a global way, Vigotski and the man's conception as someone who transforms and is transformed in relationships arising from a particular culture, respecting and recognizing the differences, and Michel Foucault regarding the "discipline and docile bodies notion" due to the fact that the school is compared to the barracks, prisons, hospitals, because of employed hierarchy and normalizing sanctions.
Keywords: autism spectrum disorder inclusive special education body learning